Analysis of University STEM Students' Mathematical, Linguistic, Rhetorical-Organizational Assignment Errors - María-José Arévalo; María Asun Cantera; Vanessa García-Marina; Marian Alves-Castro (MDPI AG, 2021)
Although Error Analysis (EA) has been broadly used in Foreign Language and Mother Tongue learning contexts, it has not been applied in the field of engineering and by STEM (Science, Technology, Engineering, and Mathematics) students in a systematic way. In this interdisciplinary pilot study, we applied the EA methodology to a wide corpus of exercises and essays written by third-year students of mechanical engineering, with the main purpose of achieving a precise diagnosis of the students' strengths and weaknesses in writing skills. For the analysis to be as exhaustive as possible, the errors were typologized into three main categories (linguistic, mathematical, and rhetorical-organizational), each of which is, in turn, subdivided into 15 items. The results show that the predominant errors are rhetorical-organizational (39%) and linguistic (38%). The application of EA permits the precise identification of the areas of improvement and the subsequent implementation of an educational design that allows STEM students to improve their communicative strategies, especially those related to the writing skills and, more precisely, those having to do with the optimal use of syntax, punctuation, rhetorical structure of the text, and mathematical coherence.